Judging 'Best Available Science': Emerging Issues and the Role of Experts. (23rd April 2018) - Cook, Kate
Abstract: This article considers the implications, for future disputes, of the adoption of the best available science (BAS) standard in a number of international (and national) regimes, including the 2015 Paris Agreement on Climate Change. The three strands of BAS: 'best', 'available', 'science' raise distinct but related issues on which expert evidence may be presented before courts and tribunals. This article considers these three aspects of BAS, both in relation to the evidence which states and others may need to present to demonstrate substantive conformity with BAS, and in relation to the way in which expert evidence is appraised by tribunals in such disputes.